2022
DOI: 10.3390/vaccines10050708
|View full text |Cite
|
Sign up to set email alerts
|

Could SARS-CoV-2 Have Bacteriophage Behavior or Induce the Activity of Other Bacteriophages?

Abstract: SARS-CoV-2 has become one of the most studied viruses of the last century. It was assumed that the only possible host for these types of viruses was mammalian eukaryotic cells. Our recent studies show that microorganisms in the human gastrointestinal tract affect the severity of COVID-19 and for the first time provide indications that the virus might replicate in gut bacteria. In order to further support these findings, in the present work, cultures of bacteria from the human microbiome and SARS-CoV-2 were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 34 publications
5
76
0
Order By: Relevance
“…(2) SARS-CoV-2 infection was found to downregulate the expression of angiotensin-converting enzyme 2 (ACE2) and B0AT1 (a molecular ACE2 chaperone) on the luminal surfaces of intestinal epithelial cells, which may facilitate the growth of the pathogens 25 , 113 , 114 . (3) An in vitro study found that SARS-CoV-2 might directly infect bacteria 115 . In the second part, we propose that specific intrinsic ‘microbiome signatures’ at the point of SARS-CoV-2 infection could influence the severity of infection and host immune response by several putative mechanisms: (i) increased opportunistic pathogens might be further recognized by innate lymphocytes and intensify gut pro-inflammatory responses 185 .…”
Section: Covid-19 and Gut Microbiotamentioning
confidence: 99%
“…(2) SARS-CoV-2 infection was found to downregulate the expression of angiotensin-converting enzyme 2 (ACE2) and B0AT1 (a molecular ACE2 chaperone) on the luminal surfaces of intestinal epithelial cells, which may facilitate the growth of the pathogens 25 , 113 , 114 . (3) An in vitro study found that SARS-CoV-2 might directly infect bacteria 115 . In the second part, we propose that specific intrinsic ‘microbiome signatures’ at the point of SARS-CoV-2 infection could influence the severity of infection and host immune response by several putative mechanisms: (i) increased opportunistic pathogens might be further recognized by innate lymphocytes and intensify gut pro-inflammatory responses 185 .…”
Section: Covid-19 and Gut Microbiotamentioning
confidence: 99%
“…[ 19 , 682 ]). To this end, the suggestion of Brogna et al [ 683 ] that SARS-CoV-2 could act like a bacteriophage and use bacteria as replication hosts is of especial interest. The gut microbiome does of course contain many trillions of organisms [ 684 , 685 ], contributes massively to immunity and inflammation [ 686 ], provides a clear pathway between diet and health [ 687 ], and would be the most logical place for such a reservoir to persist.…”
Section: A Gut Microbiome Reservoir For Sars-cov-2?mentioning
confidence: 99%
“…The bacterial GRP78 is essentially required for proper bacterial growth and mRNA/protein [ 84 ], and is a therapeutic target for both bacterial and viral infection [ 85 ]. Of note, SARS-CoV-2 is detected alive in feces specimens from COVID-19 patients [ 3 , 4 ]; SARS-CoV-2 has bacteriophage-like behavior, replicating in bacteria [ 86 ]; SARS-CoV-2 infection impairs gastrointestinal (GI) microbiota, which is associated with COVID-19 severity [ 87 ]. These data suggest that the interaction of GRP78 with SARS-CoV-2 could contribute to replication/transmission by GI/fecal bacteria, impair the microbiota, and affect the severity of COVID-19.…”
Section: Other Pathological Traits Of Grp78 For Sars-cov-2mentioning
confidence: 99%